Acoso sexual y estrés postraumatico en una mujer de 23 años de edad de la ciudad de Milagro - Gastesi Bajaña, Alisson Odalis (2021)
This case study details a 23-year-old woman living in the city of Milagro who, after suffering sexual harassment in public transport, manifests with different symptoms of PTSD and how these negatively affect her life. With this revelation of the patient and with the knowledge acquired, it was possible to work on the different triggering components such as the behavioral area, the affective area, the cognitive area and the somatic area. In this way, this patient is exposed to fear and manages to overcome it as well as reduce symptoms. For the collection of important data, several psychometric tests were applied, such as the Hamilton test and the David test, being a support to verify the frequency and intensity of the symptoms with respect to the disorder.